Evaluating a Modular Approach to Therapy for Children With Anxiety, Depression, Trauma, or Conduct Problems (MATCH) in School-Based Mental Health Care: Study Protocol for a Randomized Controlled Trial - Harmon, Sherelle L.; Price, Maggi A.; Corteselli, Katherine A.; Lee, Erica H.; Metz, Kristina; Bonadio, F. Tony; Hersh, Jacqueline; Marchette, Lauren K.; Rodríguez, Gabriela M.; Raftery-Helmer, Jacquelyn; Thomassin, Kristel; Bearman, Sarah Kate; et al. (Frontiers in Psychology, 2021)
Introduction: Schools have become a primary setting for providing mental health care to youths in the U.S. School-based interventions have proliferated, but their effects on mental health and academic outcomes remain understudied. In this study we will implement and evaluate the effects of a flexible multidiagnostic treatment called Modular Approach to Therapy for Children with Anxiety, Depression, Trauma, or Conduct Problems (MATCH) on students’ mental health and academic outcomes. Methods and analysis: This is an assessor-blind randomized controlled effectiveness trial conducted across five school districts. School clinicians are randomized to either MATCH or usual care (UC) treatment conditions. The target sample includes 168 youths (ages 7-14) referred for mental health services and presenting with elevated symptoms of anxiety, depression, trauma, and/or conduct problems. Clinicians randomly assigned to MATCH or UC treat the youths who are assigned to them through normal school referral procedures. The project will evaluate the effectiveness of MATCH compared to UC on youths’ mental health and school related outcomes and assess whether changes in school outcomes are mediated by changes in youth mental health. Ethics and dissemination: This study was approved by the Harvard University Institutional Review Board (IRB14-3365). We plan to publish the findings in peer-reviewed journals and present them at academic conferences. Trial registration: ClinicalTrials.gov ID: NCT02877875. Registered on August 24, 2016.